Effects of different doses of ephedrine spinal anesthesia on hemodynamics and adverse reactions in patients undergoing transurethral resection of the prostate - Shuyue Wang; Lei Yu; Jichen Fang; Yu Jiang (BMC Urology)
Abstract Objective To investigate the effects of different doses of ephedrine spinal anesthesia on hemodynamics and adverse reactions in patients undergoing transurethral resection of the prostate (TURP). Methods Sixty patients who underwent TURP in our hospital from October 2023 to December 2024 were retrospectively selected as the research subjects. According to the different doses of ephedrine needed during the operation, the patients were divided into observation group (10 mg ephedrine, n = 30) and control group (5 mg ephedrine, n = 30). The anesthetic effect of the two groups was evaluated. The changes of hemodynamics and stress indicators of the two groups were detected and the incidence of adverse reactions was analyzed. Results Compared with the control group, the onset time of motor block and sensory block in the observation group was significantly shorter (P < 0.05), but the duration of motor block and sensory block was significantly longer (P < 0.05). The heart rate of the observation group was lower than that of the control group 10 min of administration and at the beginning of resection (P < 0.05). The diastolic blood pressure and systolic blood pressure in the observation group were higher than the control group (P < 0.05). The levels of cortisol (COR) and epinephrine (EPI) in the observation group were lower than the control group (P < 0.05). The incidence of adverse reactions in the control group was 53.33% (16/30), which was higher than 20.00% (6/30) in the observation group (P < 0.05). Conclusion The application of 10 mg ephedrine in TURP can help stabilize the hemodynamics of patients, reduce the stress response of the body, and decrease the incidence of hypotension and other adverse reactions.